A Predictive Model of 2yDFS During MR-Guided RT Neoadjuvant Chemoradiotherapy in Locally Advanced Rectal Cancer Patients - Chiloiro, Giuditta; Boldrini, Luca; Preziosi, Francesco; Cusumano, Davide; Yadav, Poonam; Romano, Angela; Placidi, Lorenzo; Lenkowicz, Jacopo; Dinapoli, Nicola; Bassetti, Michael F.; Gambacorta, Maria Antonietta; Valentini, Vincenzo (Frontiers in Oncology, 2022)
Purpose Distant metastasis is the main cause of treatment failure in locally advanced rectal cancer (LARC) patients, despite the recent improvement in treatment strategies. This study aims to evaluate the “delta radiomics” approach in patients undergoing neoadjuvant chemoradiotherapy (nCRT) treated with 0.35 T magnetic resonance-guided radiotherapy (MRgRT), developing a logistic regression model able to predict 2-years disease-free-survival (2yDFS). Methods Patients affected by LARC were enrolled in this multi-institutional study. A predictive model of 2yDFS was developed taking into account both clinical and radiomics variables. Gross Tumour Volume (GTV) was delineated on the MR images acquired during MRgRT and 1067 radiomic features (RF) were extracted using the MODDICOM platform. The performance of RF in predicting 2yDFS was investigated in terms of Wilcoxon–Mann–Whitney test and area under Receiver Operating Characteristic (ROC) curve (AUC). Results 48 patients have been retrospectively enrolled, with 8 patients (16.7%) developing distant metastases at 2 years follow up. A total of 1099 variables (1067 RF and 32 clinical variables) were evaluated in two different models: radiomics and radiomics/clinical. The best performing 2yDFS predictive model was a delta radiomics one, based on the variation in terms of area/surface ratio between BED at 54Gy and simulation (AUC of 0.92). Conclusions The results of this study suggest a promising role of delta radiomics analysis on 0.35 T MR images in predicting 2yDFS for LARC patients. Further analyses including larger cohorts of patients and an external validation are needed to confirm these preliminary results.